Comparison of central venous oxygen saturation and serum lactate clearance as predictors of outcome in septic shock patients: a prospective control trial - Narula, Gagan Kumar; Singh, Ajit Kumar; Adya, Anish (International Journal of Research in Medical Sciences, 2018)
Background: Sepsis is the leading causes of mortality and morbidity in ICU. Early recognition and intervention ensures speedy recovery and early discharge. It’s possible only if good predicting parameters indicating optimum resuscitation are available. Lactate level reduction and ScvO2 level in the jugular vein can be utilized as predictors. Methods: In this prospective study after applying exclusion inclusion criteria, 99 patients were selected and randomized into 2 groups. In one group reduction in lactate levels and in other ScVo2 levels were used as a predictor of resuscitation. Therapeutic interventions, Hospital stay, ICU Stay and 28-day mortality were compared in both groups. Statistical analysis was carried out by SPSS software. Results: On comparison of demographic profile, morbidity, SOFA score and hemodynamic parameters, there was insignificant difference (P >0.05). No significant difference in the number of vasopressors, Average Hospital or ICU Stay (Group A is 10.68±21.46 while Group B is 9.49±17.22) and 28-day mortality rate (in Gp A 60% vs group B 57.1) was observed. Mean crystalloids administered in group A was 4.93±1.11 liters, significantly more than group B i. e. 4.19±1.17 liters. (P<0.05) which was statistically significant. Conclusions: Although both parameters of resuscitation are used widely and sometimes simultaneously, in this study lactate and ScvO2 both used and compared in a similar set of patients, appeared to be equivocal in term of 28-day mortality, except the volume of crystalloids required was more in ScvO2 Group.